Beneficial Actions of Essential Fatty Acids in Streptozotocin-Induced Type 1 Diabetes Mellitus - Shen, Junhui; Zhang, Li; Wang, Yuanqi; Chen, Zhiqing; Ma, Jian; Fang, Xiaoyun; Das, Undurti N.; Yao, Ke (Frontiers in Nutrition, 2022)
The essential fatty acids (EFA) n3 alpha-linolenic acid (ALA) and n6 linoleic acid (LA) are of benefit in diabetes mellitus, but their mechanisms of action are unknown. We therefore examined the effects of EFAs on the metabolism, gut microbiota, and inflammatory and retinal histopathology indices in streptozotocin (STZ)-induced type 1 diabetes mellitus (T1DM) animals, and we assessed the levels of vitreal lipoxin A4 (LXA4)—derived from LA—in subjects with diabetic retinopathy (DR). STZ-induced T1DM rats received LA or ALA 100 ug/day intraperitoneally on alternate days for 21 days, and their blood glucose; lipid profile; plasma, hepatic, and retinal fatty acid profiles (by gas chromatography); retinal histology; activities of hepatic and retinal desaturases; and inflammatory markers (by qRT-PCR) were evaluated. Gut microbiota composition was assayed by 16S rDNA sequencing technology of the fecal samples, and their short-chain fatty acids and bile acids were assayed by gas chromatography and liquid chromatography, respectively, coupled with tandem mass spectrometry. The human vitreal fatty acid profiles of subjects with proliferative DR and LXA4 levels were measured. LA and ALA significantly improved the plasma glucose and lipid levels; increased the abundance of Ruminococcaceae (ALA-treated group), Alloprevotella, Prevotellaceae_Ga6A1_group, Ruminococcaceae_UCG_010, and Ruminococcus_1 (LA-treated group) bacteria; enhanced acetate and butyrate levels; and augmented fecal and hepatic concentrations of cholic acid, chenodeoxycholic acid, and tauro ursodeoxycholic acid in ALA- and LA-treated animals. Significant STZ-induced decreases in plasma LA, gamma-linolenic acid, arachidonic acid, and ALA levels reverted to near normal following LA and ALA treatments. Significant changes in the expression of desaturases; COX-2, 5-LOX, and 12-LOX enzymes; and cytokines in T1DM were reverted to near normal by EFAs. DR subjects also had low retinal LXA4 levels. The results of the present study show that ALA and LA are of significant benefit in reversing metabolism, gut microbiota, and inflammatory and retinal index changes seen in T1DM, suggesting that EFAs are of benefit in diabetes mellitus.